Three-corridors procedure to operate in the infralabyrinthine cervico-jugulo-carotico-tympanic area - Altın, Gökhan; Bayazıt, Yıldırım Ahmet (Karger, 2022)
Introduction: The aim of the study was to present the results of our experience in three-corridors procedures applied for the tumors and inflammatory lesions of the infralabyrinthine cervico-jugulo-carotico-tympanic area. Methods: The lesions located in the infralabyrinthine cervico-jugulo-carotico-tympanic area were operated in 13 patients using the 3-corridors technique. The anatomical and functional integrity of the external and middle ears and the facial nerve (FN) could be preserved. Results: The diagnoses were glomus jugulare, infralabyrinthine petrous bone cholesteatoma, jugular foramen schwannoma, and giant-cell tumor. The follow-up duration ranged from 2 to 24 months. No tumor recurrence or growth was encountered in the follow-up. The operations were uneventful. Total surgical excision could be achieved in 10 patients. A second-stage retrosigmoid approach was performed for the total removal of the intracranial tumor remnant in two patients. A wait-and-scan policy has been considered in one patient who had partial resection for a glomus jugulare tumor. Conclusion: Three-corridors procedure seems to be a useful technique to operate in the infralabyrinthine, cervico-jugulo-carotico-tympanic area as it takes the advantage of hearing preservation, preservation of the anatomic and functional integrity of the external and middle ear structures as well as the FN.
Keywords: Acoustic Neuroma; Cholesteatoma; Glomus Jugulare; Jugular Foramen Tumor; Skull Base Surgery